2019
DOI: 10.3389/fgene.2019.01190
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Resequencing Reveals Selection Signatures Associated With Important Traits in Ethiopian Indigenous Goat Populations

Abstract: Ethiopia is considered as the main gateway for the introduction of livestock species, including goat, to the African continent. Ethiopian goats are characterized by their unique adaptive ability, and different physical characteristics in terms of morphology, body size, coat colors, and other important traits. The comparative population genomic analysis provides useful genomic information associated with important traits. Whole-genome resequencing of 44 Ethiopian indigenous goats produced 16 million single-nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…In our dataset, the two cosmopolitan breeds (Saanen and Camosciata delle Alpi) reported this HRR island in which several mapped genes have a role in livestock production. In particular, the PPP4R3B gene was associated to thermotolerance in the African N’Dama cattle breed 52 ; Berihulay et al 53 found this gene involved in gluconeogenesis and lipidic metabolism in Abergelle goats. The PNPT1 gene was reported implicated into RNA transport in pigs 53 and Bandur sheep 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our dataset, the two cosmopolitan breeds (Saanen and Camosciata delle Alpi) reported this HRR island in which several mapped genes have a role in livestock production. In particular, the PPP4R3B gene was associated to thermotolerance in the African N’Dama cattle breed 52 ; Berihulay et al 53 found this gene involved in gluconeogenesis and lipidic metabolism in Abergelle goats. The PNPT1 gene was reported implicated into RNA transport in pigs 53 and Bandur sheep 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the PPP4R3B gene was associated to thermotolerance in the African N’Dama cattle breed 52 ; Berihulay et al 53 found this gene involved in gluconeogenesis and lipidic metabolism in Abergelle goats. The PNPT1 gene was reported implicated into RNA transport in pigs 53 and Bandur sheep 54 . Previous studies linked the EFEMP1 gene with traits of interest in livestock species.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research has been undertaken on the genetics of African indigenous goats using microsatellite 9 – 18 and SNP microarray genotypes 19 – 23 , relatively few studies have been conducted on these breeds using whole-genome sequencing (WGS) information. For example, for the African continent, WGS are only publicly available in the vargoats database ( https://www.goatgenome.org/vargoats.html ) including for Ethiopia (73 genome sequences of eight breeds) 24 , Morocco (44 genome sequences from three breeds) 25 , Kenya (15 sequences from two breeds), Madagascar (35 sequences from four breeds), Mali (36 sequences from six breeds), Malawi (24 sequences from five breeds), Mozambique (23 sequences from five breeds), Tanzania (39 sequences from five breeds), Uganda (three sequences from one breed), Zimbabwe (20 sequences from two breeds) and Nigeria (three sequences from two breeds) ( https://ncbi.nlm.nih.gov/ ). These publicly accessible genome data are important for (i) studying population-level genetic diversity and structure, (ii) understanding domestication and evolutionary history, (iii) detecting adaptation selective sweeps, and (iv) discovering variants (SNPs, structural variants, causative mutations e.t.c.)…”
Section: Background and Summarymentioning
confidence: 99%
“…Over the last decade, many genome-wide selection signatures have been detected in different goat breeds that are associated with production (Wang et al, 2016), liter size (Lai et al, 2016;Guang-Xin et al, 2019;Tao et al, 2021;Wang et al, 2021), adaptation (Kim et al, 2016;Wang et al, 2016), disease resistance (Lee et al, 2016), cashmere fiber (Li et al, 2017) and multiple traits (Guo et al, 2018). However, there are no such studies on the Ethiopian indigenous goats except Berihulay et al (2019) whohowever, analyzed only two Ethiopian goat populations, Abergelle and Begait. In general, the studies have demonstrated how positive selection acting on complex traits has changed the genetic composition of domestic goats.…”
Section: Introductionmentioning
confidence: 99%